Behavior and strength of reinforced concrete flanged deep beams with web openings. (October 2020) - El-Kareim, Ata; Arafa, Ahmed; Hassanin, Amal; Atef, Mohamed; Saber, Ahmed
Abstract: A Considerable research work has investigated the behavior and strength of deep beams with transverse openings. However, the focus was mainly on deep beams with rectangular sections, while no experimental data are available on the behavior of flanged deep beams. As result, most design codes and guidelines neglect the effect of flange on the strength and stiffness of deep beams with openings. This study aims to enrich the literature by reporting the experimental data of sixteen deep beams: twelve with flanged section (with or without opening) and four reference beams with rectangular section. The shear span to depth ratio (a/d) was 1.10. The openings in the beams' web had a constant depth (120 mm) and varied lengths (120 mm, 240 mm, and 360 mm). The effect of flange on the strength, stiffness, and deformation capacity of the tested beams was assessed. The results were analyzed in terms of cracking pattern, mode of failure, load–deflection behavior, deformations distribution, and strains in reinforcement. Prediction of the experimentally obtained behavior using finite element model was introduced. Assessment of ultimate strengths based on the available design equations and analytical models was also discussed. The test results clearly showed that the flange resulted in a significant gain in the strength and stiffness that cannot be ignored in the design. The FEA was shown to provide a reasonably accurate estimation of the experimental behavior for the tested beams. With the assumptions made herein, the modified compression field theory (MCFT) prediction was the closest to the experimental results.